The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.eupc.2005.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of pocket related complications with fibrin sealant in patients undergoing pacemaker implantation who are receiving anticoagulant treatment

Abstract: Fibrin sealant is an effective haemostatic agent. The results obtained in our study show that the administration of fibrin sealant in patients receiving anticoagulant treatment eliminates postoperative haematomas after pacemaker implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
1
34
0
3
Order By: Relevance
“…Topical fibrin sealants reduce hematoma formation in anti-coagulated patients undergoing device procedures, but their effect on DRI is unknown. 79 Cephalic cut down has theoretical advantages in reducing post-operative bleeding by avoiding inadvertent arterial puncture. 80 In the event of failed cephalic access or when additional venous access is required ultrasound guided vascular access may also reduce the risk of arterial puncture.…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Topical fibrin sealants reduce hematoma formation in anti-coagulated patients undergoing device procedures, but their effect on DRI is unknown. 79 Cephalic cut down has theoretical advantages in reducing post-operative bleeding by avoiding inadvertent arterial puncture. 80 In the event of failed cephalic access or when additional venous access is required ultrasound guided vascular access may also reduce the risk of arterial puncture.…”
Section: Operative Considerationsmentioning
confidence: 99%
“…12,13 Alternatively, fibrin sealant has been proposed as a useful agent to reduce risk of hematoma. 14 In any case, aggressive management with compression will minimize the risk of wound dehiscence. It is advisable only in the rare cases in which closure line integrity is threatened to surgically evacuate a hematoma, because opening the pocket at that juncture greatly increases the subsequent risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although this increase was not statistically significant, the use of D-Stat Flowable was prematurely stopped by our institutional clinical event committee during a planned interims analysis. The reason for this somewhat unexpected observation is unclear, previous studies reported no infectious complications [15], or only report on "pocket related complications" in general without providing results for infectious complications [11]. However, research focused on the addition of antibiotics to hemostats in order to provide local antimicrobial effect during tissue healing was performed in the late 1980s and early 1990s.…”
Section: Pocket Infection and Local Haemostat Usementioning
confidence: 68%